The Effect of Institusional Ownership, Managerial Ownership, Profitability and Audit Quality on Tax Agressivity - Muhammad Zaid Al Fikri; Herlin Tundjung Setijaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this study is to analyze the causality relationship, which explains the independent variables consisting of institutional ownership, managerial ownership, profitability and audit quality against the dependent variable of tax aggressiveness. The data analysis of this research is quantitative analysis and uses Eviews software. EViews is software used for statistical analysis and econometrics. EViews allows users to process data, test hypotheses, and create statistical models for data analysis. EViews methods include the use of time series and cross-sectional data to perform regression analysis, multivariate analysis, causality testing, and data stationary testing. EViews can also be used to design, test, and estimate econometric models such as linear regression models, autoregressive models, and mobile autoregressive models. The results of this study show that the pattern of data that has been collected and the results of testing that has been carried out using Eviews 12 with the panel data regression analysis method show that first, institutional ownership has a negative and significant effect on tax aggressiveness. Second, managerial ownership has a significant negative effect on tax aggressiveness. Third, profitability has a significantly positive effect on tax aggressiveness. Fourth, audit quality has a significant negative effect on tax aggressiveness. Keywords: institutional ownership, managerial ownership, profitability and quality checks on tax aggressiveness